Graphene engineering by neon ion beams. (18th February 2016) - Iberi, Vighter; Ievlev, Anton V; Vlassiouk, Ivan; Jesse, Stephen; Kalinin, Sergei V; Joy, David C; Rondinone, Adam J; Belianinov, Alex; Ovchinnikova, Olga S
Abstract: Achieving the ultimate limits of lithographic resolution and material performance necessitates engineering of matter with atomic, molecular, and mesoscale fidelity. With the advent of scanning helium ion microscopy, maskless He + and Ne + beam lithography of 2D materials, such as graphene-based nanoelectronics, is coming to the forefront as a tool for fabrication and surface manipulation. However, the effects of using a Ne focused-ion-beam on the fidelity of structures created out of 2D materials have yet to be explored. Here, we will discuss the use of energetic Ne ions in engineering graphene nanostructures and explore their mechanical, electromechanical and chemical properties using scanning probe microscopy (SPM). By using SPM-based techniques such as band excitation (BE) force modulation microscopy, Kelvin probe force microscopy (KPFM) and Raman spectroscopy, we are able to ascertain changes in the mechanical, electrical and optical properties of Ne + beam milled graphene nanostructures and surrounding regions. Additionally, we are able to link localized defects around the milled graphene to ion milling parameters such as dwell time and number of beam passes in order to characterize the induced changes in mechanical and electromechanical properties of the graphene surface.